PENGEMBANGAN MEDIA PEMBELAJARAN COMIC BERBASIS COMIC LIFE MATERI BENTUK-BENTUK ENERGI UNTUK MENDUKUNG MERDEKA BELAJAR SISWA KELAS IV SEKOLAH DASAR - Yulia Darniyanti; Aspialana; Estuhono (STKIP Subang, 2023)
Education is the process of a person developing all the abilities both intellectual and emotional, attitudes, and behaviors he has. Education can also be interpreted as the process of changing the attitudes and behaviors of a person or group of people with the aim of maturing through teaching media. Education is the main key in improving the quality of a nation. This research aims to create a comic learning media. This study uses the type of research and development (R &; D) this researcher uses the ADDIE model (analyze, design, dpelovment, implementation, and evaluation) the type of data taken in this study is quantative and qualitative data. The instruments used in this study are validation sheets, practicality sheets and effectiveness sheets. Data collection techniques used using observation techniques. Interviews and documentation. Data analysis in the form of validity analysis, practicality analysis and effectiveness analysis. The results of the validity of comic learning media assessed by validators amounted to 3 people, showing that comic learning media obtained a percentage of 85.83%. With a very valid category, comic learning media is suitable for use and in accordance with the provisions of SD Negeri 04 Koto Baru. Practicality assessed from teacher response questionnaires and student response questionnaires to comic learning media obtained the following percentages: teacher response questionnaire 96% with very practical category, student response questionnaire 93.05% with very practical category, so based on the analysis of the teacher response questionnaire and student response questionnaire, it can be concluded that comic learning media is very practical for science learning in the SDN Negeri 04 koto baru class. The effectiveness assessed from the test question results obtained a percentage of 80% with the effectiveness category so that it can be said that using comic learning media is able to achieve learning objectives.